2022
DOI: 10.5219/1712
|View full text |Cite
|
Sign up to set email alerts
|

The study of the intensification of technological parameters of the sausage production process

Abstract: One of the sources of sodium are meat products. Increased consumption of meat products and sodium intake leads to serious health problems. The task of reducing the dosage of sodium chloride in minced meat needs to be addressed. The partial replacement of table salt with sea salt will reduce the sodium concentration in products to 20%. It is established that this modification increases the moisture-binding properties of minced meat and lowers the dosage of salt in the mass of raw meat, which will reduce the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Thus, the IC50 (average inhibitory concentration is the concentration of the drug that suppresses a certain cellular function by 50%) of disinfectants based on the effect on the culture of intestinal origin (HT-29) is Biodez -60.93 ±9.81 μl/l, Blanidas -264.30 ±25.12 μl/l, Virkon-S -283.59 ±31. 20 We used the HEK 293 (Human Embryonic Kidney) cell line as a kidney model to determine the organ-specific toxicity of the studied disinfectants (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the IC50 (average inhibitory concentration is the concentration of the drug that suppresses a certain cellular function by 50%) of disinfectants based on the effect on the culture of intestinal origin (HT-29) is Biodez -60.93 ±9.81 μl/l, Blanidas -264.30 ±25.12 μl/l, Virkon-S -283.59 ±31. 20 We used the HEK 293 (Human Embryonic Kidney) cell line as a kidney model to determine the organ-specific toxicity of the studied disinfectants (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The appearance, taste, and smell of the ice cream "Banana & Pistachio" are improved due to the addition of banana, which gives the product a sweetish taste and a good smell compared to control one 1, which is too sweet because of high content of sugar and additional sweetening syrups [27], [28]. These parameters of the ice cream "Coffee and chocolate" are improved due to the addition of coffee beans, which give the product a saturated brown color and a good coffee taste [29]. Similar results were achieved in the research еffect of coconut milk, tender coconut and coconut sugar on ice cream's physicochemical and sensory attributes [51].…”
Section: Resultsmentioning
confidence: 99%
“…The absolute speed value of the working container is: (9) The oscillation amplitude of the working container is: (10) Using the formula (10), we construct the amplitude-frequency characteristics of the oscillation system under study. In this case, we vary the ratio of m1/m2 (Figure 2) for a fixed value of the eccentricity е of the drive shaft; as well as the amplitude-frequency characteristics of the container of the vibrating massager when changing the eccentricity е at a fixed ratio m1/m2 (Figure 3).…”
Section: Sample Of Hammentioning
confidence: 99%
“…To intensify these processes when producing the meat products after the technological operation of the meat injection, the use of vacuum and vibration impact during the massage of the meat raw materials is becoming more common, which justifies the research's relevance. Domestic and foreign researchers, particularly, have shown that the proteolytic enzyme preparations of animal, vegetable, and microbial origin and own enzymes of the meat can affect the proteins and simultaneously increase the functional and technological properties of the raw materials as well as improve the organoleptic and structuralmechanical performance of the finished products [9]. An outstanding contribution to the development of the vibration technologies for implementing the mixing processes and uniform distribution of the components of the meat raw materials in the working volume, which is relevant to the technology under study, was made by wellknown domestic and foreign scientists [10].…”
Section: Introductionmentioning
confidence: 99%